2022
DOI: 10.1002/adbi.202200131
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative System Modeling Bridges the Gap between Macro‐ and Microscopic Stomatal Model

Abstract: An understanding of stomatal function is vital for the carbon and water cycle in nature. In the past decades, various stomatal models with different functions have been established to investigate and predict stomatal behavior and its association with plants’ responses to the changing climate, but with limited biological information provided. On the other hand, many stomatal models at the molecular level focus on simulating and predicting molecular practices and ignore the dynamic quantitative information. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…This imbalance negatively affects both CO 2 assimilation and water loss (Lawson & Blatt, 2014; Lawson & Vialet‐Chabrand, 2019). Consequently, accelerating g s kinetics is a potentially viable approach to enhancing crop iWUE, especially when compared to the complexity of genetic engineering of the photosynthetic system (Blum, 2009; Lawson et al ., 2011; Lawson & Blatt, 2014; Rui et al ., 2022). Recent studies have demonstrated that it is feasible to improve WUE without a carbon fixation penalty by engineering K + channels in guard cells (GCs), thereby accelerating stomatal kinetics (Papanatsiou et al ., 2019; Horaruang et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This imbalance negatively affects both CO 2 assimilation and water loss (Lawson & Blatt, 2014; Lawson & Vialet‐Chabrand, 2019). Consequently, accelerating g s kinetics is a potentially viable approach to enhancing crop iWUE, especially when compared to the complexity of genetic engineering of the photosynthetic system (Blum, 2009; Lawson et al ., 2011; Lawson & Blatt, 2014; Rui et al ., 2022). Recent studies have demonstrated that it is feasible to improve WUE without a carbon fixation penalty by engineering K + channels in guard cells (GCs), thereby accelerating stomatal kinetics (Papanatsiou et al ., 2019; Horaruang et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%